Meta-thematic analysis of quality in early childhood education and care - Saglam, Mehmet; Celik, Osman Tayyar; Tunc, Yunus; Kahraman, Umit; Acar, Davut; Candemir, Burcu (Springernature, 2023)
Quality in early childhood education and care (ECEC) has drawn the attention of researchers and practitioners due to its correlation with positive individual, societal, and economic results. In ECEC, however, there is no consensus on quality metrics. This meta-thematic study seeks to provide a framework for quality indicators in ECEC and to identify the contextual factors that influence the perception of quality. The study's data source comprises 14 published papers conducted in 11 countries using qualitative or mixed methods on quality in ECEC. As a consequence of the analysis, 16 early childhood education and care quality indicators were identified. As a result of the second-level studies, the underlying or associated syntheses in the ECEC quality indicators were uncovered. These include child-centeredness, teacher qualifications, culture and atmosphere of the ECEC center, holistic development, and leadership. In addition, it was concluded that cultural values and beliefs, the centralization degree of the education system, and the expectations of stakeholders are contextual elements that influence the quality and perceptions of quality in ECEC.